A mixed type boundary-value problem related to the electrostatics of cold plasma jet reactors based on dielectric barrier discharge - Vafeas, Panayiotis; Papadopoulos, Polycarpos K.; Svarnas, Panagiotis (Zielona Góra: Uniwersytet Zielonogórski)
A semi-analytical model is presented for the determination of the electric field in reactors used for cold atmospheric pressure plasma (CAPP) jet production, based on the concept of dielectric barrier discharge (DBD). These systems are associated with various applications in contemporary engineering, ranging from material processing to biomedicine, and at the same time they provide many challenges for fundamental research.
Keywords: DBD; cold plasma jet; reactor; mixed-type boundary-value problem; electrostatic potential theory